WORK MOTIVATION AND WORKLOAD ON NURSES’ CARING BEHAVIOR IN EMERGENCY ROOM - Nugraha, Dedep; Situmorang, Roganda; Sholihatul Mukaromah, Raihany (Jurnal Kesehatan Kusuma Husada, 2025)
Indonesia has a high accumulation of patient visits to the Emergency Room (ER), thus caring in the ER requires more attention to produce better quality nursing services. This study aims to see the effect of nurses' motivation and workload on caring behavior in the ER. The research method used is quantitative, with a correlation analytic research design and a cross-sectional approach. The sample consisted of 37 nurse and patient respondents using accidental sampling techniques. The instrument used was the Gadar Caring Scale (GCS-46) questionnaire with frequency distribution data analysis and the Spearman Rank statistical test. The results showed that more than half of the nurses' motivation (56,76%) was in a good category and almost half of the nurses' workload was in the heavy category (40.54%). On the other hand, the level of nurses' caring was almost entirely in the moderate category (94.59%). In addition, there was a correlation between nurse’s motivation and caring as indicated by the correlation coefficient (r) and p-value of 0.55 and 0.0237, respectively. Meanwhile, the results of the analysis between nurses' workload and caring gave r and p-values ​​of 0.11 and 0.5121, respectively, indicating that there was no relationship between nurses' workload and nurses' caring in the ER.